Childhood emotional abuse and suicidal ideation in college students: exploring the mediating role of alexithymia and the moderating effect of physical exercise - Hu, Chang; Huang, Wenying; Zhang, Wen (Frontiers in Psychiatry, 2025)
ObjectiveChildhood emotional abuse is a significant yet often overlooked predictor of suicidal ideation among young adults. This longitudinal study examined how alexithymia mediates the relationship between Childhood emotional abuse and suicidal ideation among college students, and whether physical exercise moderates both the direct and indirect paths within this association.MethodWe conducted a two-wave longitudinal study (12-month interval) using convenience sampling of Chinese college students from multiple universities in Yunnan and Guizhou provinces. At T1 (April–June 2024), 1,006 valid online self-reports were collected; at T2 (April–June 2025), 926 participants were successfully matched (Mage = 20.78, SD = 2.58). Measures included childhood emotional abuse (CTQ–Emotional Abuse), alexithymia (TAS-20), suicidal ideation (PANSI), and weekly physical exercise frequency (single-item). Analyses used SPSS PROCESS (Model 4 and 15) with 5,000 bootstrap resamples, controlling for gender and birthplace.ResultsThe results showed that T2 alexithymia mediated the relationship between T1 childhood emotional abuse and T2 suicidal ideation. Additionally, T2 physical exercise significantly moderated the direct relationship between T1 childhood emotional abuse and T2 suicidal ideation. However, the moderating effect of physical exercise on the indirect pathway via T2 alexithymia was not significant.ConclusionsThe findings highlight alexithymia as a key psychological mechanism linking emotional abuse in Childhood to suicidal ideation during emerging adulthood, while physical exercise serves as a protective factor at the direct level. Targeted interventions that enhance emotional awareness and promote regular physical activity may help mitigate suicide risk among college students with emotional abuse histories.